TEORI HUKUM PROGRESIF : PENGENDALI DUNIA YANG LEPAS KENDALI - Max Boli Sabon (Faculty of Law, Universitas Diponegoro, 2013)
Anthony Giddens once wrote that the impact of globalization causes the world run away. The world runs away hurriedly, ramblingly, uncertainly, finally arrives in Indonesia in the form of corruption, as a super extra ordinary crime. It is hard to find the entry point of the movement in order to control it. The question is, if it is possible to control the world in this event? By using the approach of the theory of progressive law, including its vision and methods, it is indeed possible to try. The result of study arrives at a conclusion that corruption is now reaching a level where it can be described as running beyond control, and it may be controllable starting from the prime stage by means of the vision of progressive law, at the optimum stage, by means of the methods of progressive law, and finally at the ultima stage with the strength of the double mix of mind and heart.